Idosos em acolhimento institucional: perfil sociodemográfico e capacidade funcional - SILVA, Tatiane Bahia do Vale (Universidade Federal do Pará, 2019)
Long Term institutions for Elderly are emerging alternatives care unfamiliar. This research analyzes the demographic profile and functional capacity of elderly in residential care situation in Belém /Pará. It addresses on a descriptive, cross-sectional, and quantitative. 73 seniors were attended in two public institutions, and they were assessed by the Mini Mental State Examination (MMSE), Katz Index and Lawton and in cases of the presence of cognitive decline, the scale of the Disability Assessment for Dementia (DAD). According to the research some aspects were noticed as, the predominance of females (53